(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2023)
Documents are one of the most widely used forms of evidence in court, whether in the civil court or the Syariah court in Malaysia. The characteristics of documents, such as their permanent nature, render them as the primary choice compared to other methods of proof. However, the issue of accepting documents as a method of proof relates to the authenticity of the said evidence presented in Court. This is because if a document’s authenticity is doubted, the Court will reject the exhibit to be admitted as evidence and instead require other supporting proof. Forensic science is the application of the modernity of science in helping to solve various problems, including ensuring the authenticity of a document. In this article, the researcher discusses the concepts, issues and challenges of submitting documentary evidence in Malaysian Syariah courts. To achieve the study’s objective, the researcher used a qualitative approach via document analysis from primary and secondary data. The data obtained were then analyzed using the document analysis method and presented as sub-themes. The findings show that the application of forensic science in documentary evidence is viewed as highly important, especially in dealing with issues related to its authenticity as proof and as an initial step to prevent the falsification of documents from occurring. In addition, Malaysian Syariah courts have generally adopted scientific evidence based on Practice Direction No. 4 of 2020, and further studies need to be carried out, primarily concerning with the formation of guidelines and provisions related to their submission in Malaysian Syariah courts. Keywords: Documents, evidence, methods of proof, forensic science, authenticity, Syariah Court Full text: PDF